Structure of Tl(18-crown-6){Cl 3 CC(O)N P(O)(OCH 3 ) 2 }: Coordination of the Ionic Multidentate Weakens the Interaction of the Metal Atom with the Crown Ether - Victor A. Trush; Konstantin V. Domasevitch; Vladimir M. Amirkhanov; Joachim Sieler (Zeitschrift für Naturforschung B, 1999)
The thallium(I) dimethyl-N-trichloroacetylamidophosphate complex with a 18-crown-6 of the composition Tl(18-crown-6)L (L = {Cl 3 CC(O)NP(O)(OCH 3 ) 2 } - ) has been prepared and characterized by means of IR spectroscopy and X-ray diffraction (orthorhombic, space group P2 1 2 1 2 1 with a = 8.660( 1), b = 11.557(2), c =26.296(3) Å, Z = 4, V = 2631.8(6) Å 3 ; R1 = 0.0285 and wR2 = 0.0558 for 4314 unique reflections). It was shown that (L - ) is coordinated to the central atom in a bidentate manner via oxygen atoms of phosphoryl [Tl-O(l) 2.678(4) Å] and carbonyl groups [Tl-O(2) 3.012(6) Å.The Tl( 18-crown-6) + moiety adopts a typical “sunrise” coordination with the metal atom laying 1.134(2) Å above the mean plane of the oxygen atoms of the macrocycle. This deviation is the highest value of the structurally examined Tl( 18- crown-6 ) + complexes. The Tl-O (etheric) separations are in the range 2.913(4) - 3.198(5) Å (av. 3.030(6) Å).